Effect of inoculum size and glucose concentration for bacterial cellulose production by Lactobacillus acidophilus - N. S., Jeff Sumardee; A. R., Mohd Hairul; Siti Hatijah, Mortan (IOP Publishing, 2020)
Bacterial cellulose (BC) has gained interest as new industrial materials because of its unique properties compared to other cellulose sources. Intense researches have been done to study the production of BC and finding a new strain source to meet the requirement of high yield of production with a low economic cost. In this work, the potential of Lactobacillus acidophilus as a new source of bacterial cellulose was studied by observing the effects of inoculum size and glucose concentration on the production of BC using the one-factor-at-time method. L. acidophilus was cultured in HS medium for 14 days at various cultivation conditions according to the experimental set-up. The results obtained indicate that the glucose concentration in the medium and the inoculum size of the bacteria had a significant role in the BC production. The highest BC of 1.843 g/L was achieved at 1.5 w/v% glucose concentration and 0.856 g/L at 6 v/v% of inoculum size. Although the amount of BC produced was comparatively low than BC produced from other bacterial strains, these results demonstrated the potential of L. acidophilus as a new strain source for BC production. Further study on other cultivation parameters is essential for the optimization of BC production by this L. acidophilus strain.